Enhancing Debt Transparency by Strengthening Public Debt Transaction Disclosure Practices - World Bank (Washington, DC: World Bank, 2022)
Improving debt transparency is critical for promoting debt sustainability and creditworthiness assessments, increasing the accuracy of public debt information, and protecting the interests of a diverse range of stakeholders. The importance of debt transparency, the costs associated with the lack of it, and its benefits, are extensively discussed in recent World Bank literature. One of the key factors that limits debt transparency as it relates to public disclosure and the sharing of public debt-related information, is transaction-level confidentiality and disclosure practices. Challenges to disclosure have become more evident during recent debt distress among borrowing countries, and the COVID-19 pandemic. The discussion in this paper reveals issues that arise from confidentiality and disclosure practices among lenders and borrowers; and highlights how these issues cause information asymmetries and undermine the interests of stakeholders. The paper concludes by proposing concrete and actionable recommendations for the World Bank, IMF and sovereigns.